Targeted therapies and adverse drug reactions in oncology: the role of clinical pharmacist in pharmacovigilance - Fornasier, G. (Int J Clin Pharm, 2018)
Background The majority of adverse drug reactions (ADRs) reported in the summary of product characteristics (SPCs) are based on pivotal clinical trials, performed under controlled conditions and with selected patients. Objectives (1) to observe ADRs in the real-world setting and to evaluate if the supervision of the pharmacist impacts on the management of ADRs and on the satisfaction of patients; (2) to sensitise health professionals and patients on the need to increase the reporting of ADRs, in compliance with Pharmacovigilance. Setting CRO Aviano, Italian National Cancer Institute. Method From February 2013 to April 2015, we conducted an observational study enrolling 154 patients (≥ 18 years) undergoing treatment with at least one of ten targeted-therapies included in the study. Main outcome ADR reporting in the real-world setting. Patient satisfaction with clinical pharmacist support. Results Reported ADRs in the real setting do not always correspond with data described in the respective SPCs. Unknown ADRs were also identified such as hyperglycaemia with lenalidomide and sorafenib; and hypomagnesaemia with bevacizumab. We also observed a 124.3% increase in spontaneous reports. Conclusion This study shows the high value of active pharmacovigilance programs, and our results might be a starting point for developing a randomised trial which should aim to demonstrate the impact of the pharmacist on improving patient’s adherence and in measuring the difference in ADRs reports in the different arms followed or not by the pharmacist. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11096-018-0653-5) contains supplementary material, which is available to authorized users.